Pengembangan Kecerdasan Lingustik AUD di Kelompok Awal melalui Pembelajaran Bilingual di TK Fawwaz Global Islamic School - Juliati, Nurhayati (SEED: Journal of Scientific Research, 2024)
This study describes linguistic development education using bilingual learning in TK Islam Purwanida located in Mataram. Based on the research that the researchers did, bilingual learning was used to support linguistic development in children. This TK Fawwaz accepts students who are motivated by Islam, both NU and Muhammadiyah. This TK Fawwaz was established because of the background of the anxiety that there was no international standard Islamic school. The class observed is the Star class (TK A) which has 13 students, consisting of 1 female student with special needs, 6 female students and 6 male students. Bilingual learning is held in TK Fawwaz which aims to prepare students to face the ever increasing development of the times. This study was written descriptively and departed from the qualitative research that the author did, based on observations in the Star class (TK A) and structured interviews with the Principal, Deputy Principal of the Curriculum Field and 2 teachers at TK A, precisely in Class Star.